Poligeneza deformacji glacitektonicznych w utworach kenozoicznych kopalni Stanisław-Północ k. Ruska (blok przedsudecki) - wstępne wyniki badań = Polyphase glacitectonic deformations of the cenozoic deposits exposed in "Stanisław-North" opencast mine near Rusko (fore-sudetic block) - preliminary results - Hałuszczak, Andrzej (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The paper describes preliminary results of structural field investigations concerning glacitectonic deformations of the Cenozoic deposits in the "Jaroszów-North" open-cast mine near Rusko village (Fore-Sudetic Block). Considering the spatial arrangement and kinematic features of studied mesostructures, it is suggested that they were related to the two separate glaciations.
Keywords: X jubileuszowe sympozjum glacitektoniki